Analysis of Students' Difficulties Reading Skills Through Expository Text - Onibala, Mouren Klaveren; Liando, Nihta V. F; Wongkar, Yapi (Program Studi Pendidikan Bahasa Inggris, 2025)
Learning English in Indonesia has unique challenges and opportunities. English is taught in most elementary to tertiary schools as a compulsory subject. Several skills will be taught in this research regarding mastering reading. These English reading skills involve several vital aspects that students must master to understand texts effectively. The description about students difficulties in reading English text in SMA N 1 Tondano realizes the reseacher to conduct a research emphazing to what difficulties of reading skills faced by students in studying expository text. This research uses a qualitative approach which aims to understand students' difficulties in reading. The subject of this research are 20 students of XI Grade in SMA N 1 Motoling. From the aforementioned findings, there are several highly significant results regarding students' challenges in writing. Analytical expository text consists of three components, specifically thesis, argumentation, and reiteration. there are various factors that contribute to students' struggles in determining the main topic, particularly a limited vocabulary that hinders their ability to read the text and comprehend its message